PYROGALLOL AS A REAGENT FOR SPECTROPHOTOMETRIC DETERMINATION OF AMMONIUM-NITROGEN (NH -N) IN AQUEOUS SOLUTION: . (Biological Sciences - PJSIR, 2003)
Pyrogallol (1,2,3-trihydroxybenzene) is proposed as a reagent for the spectrophotometric determination of ammonium-+                                                                                                                                                                                                                                  +nitrogen (NH -N) in aqueous solution. Pyrogallol forms instantaneous pale-yellow complex with aqueous NH -N. The4                                                          +                                                                                                                                                                      44 + 4 pyrogallol/ammonium-nitrogen (P/NH -N) complex has absorption maximum (lmax) at 400nm and molar absorptivity (e) of 9.706 x 102 lmol-1 cm-1. Beer’s law is obeyed up to 5 mg NH -N ml-1. The correlation coefficient (r) is 0.9983. The+ optimum pyrogallol concentration and optimum pH are found to be 0.06%(mv-1) and 7.00, respectively. The method sensitivity is 0.063 mg NH -N ml-1. The extent of ionic interference in the use of the proposed method has also  been4quantitatively evaluated. The most tolerated ions were K+ and Cl- (7.90 x 10-3 mol l-1 maximum) and the least toleratedion was Al3+ (3.12 x 10-7 mol l-1 maximum). Recovery of NH+-N from spiked water samples shows good result (98.77%4                                                  +to 101.94%). The proposed method has been applied to the determination of NH -N in some potable waters.  Results4are in good agreement with those obtained by a standard spectrophotometric method (Nessler’s method